The safety and feasibility of transcranial direct current stimulation combined with conservative treatment for patients with cervicogenic headaches: A double-blinded randomized control study protocol - K. Jobin; C. Campbell; S.M. Schabrun; K.J. Schneider; A. Smith; C.T. Debert (Contemporary Clinical Trials Communications)
Background: Cervicogenic headaches (CGH) are common following concussion and whiplash injuries and significantly reduce patient quality of life. Conservative therapies such as ET (ET) and physiotherapy combined with injection-based therapies are cornerstones of treatment for CGH but have shown limited efficacy. Transcranial direct current stimulation (tDCS) over the primary motor cortex (M1) has shown promise in treating other chronic pain conditions. The primary aim of this trial is to evaluate the feasibility and safety of tDCS when combined with ET for the treatment of CGH. Methods: Adults (aged 18–65), blinded to treatment arm, will be randomized into one of two groups: active tDCS followed by ET or sham tDCS followed by ET. Transcranial direct current stimulation will be applied over M1 three times per week for 6-weeks and ET will be performed daily. The primary outcomes of this trial will be the feasibility and safety of the intervention. Feasibility will be defined as greater than 30 % recruitment, 70 % protocol adherence, and 80 % retention rate. Safety will be defined as no severe adverse events. Secondary exploratory outcomes will assess improvement in pain, strength, function, and quality of life. Conclusions: This trial aims to demonstrate the safety and feasibility of tDCS in combination with ET for the treatment of CGH. Cervicogenic headaches can be difficult to treat contributing to significant impairments function and quality of life. Transcranial direct current stimulation is a potential novel treatment to improve health outcomes in these patients. Registration: ClinicalTrials.gov-NCT05582616.